Ответы и объяснения

  • vlara
  • середнячок
2012-11-15T17:44:26+00:00

2x-6-5=4x

2x=-11

x=-5.5

Ответ: -5,5

 

 

x(x-5)+(x+5)^{2}=50

x^{2}-5x+x^{2}+10x+25=50

2x^{2}+5x-25=0

x=(-5+15)/4  и x=(-5-15)/4

x=-5 (не удовлетворяет одз) и x=2.5

ответ 2,5

2012-11-15T17:59:14+00:00

2(х-3)-5=4х

2х-6-5-4х=0

-2х=11

х=-5.5

 

\frac{x*(х-5)}{(х+5)*(х-5)} + \frac{(x+5)(х+5)}{(Х-5)(х+5)} = \frac{50}{х^2-25}


 \frac{x^2-5x+x^2+25-50}{x^2-25}=0


\frac{2x^2-5x-25}{x^2-25}=\frac{2(x-5)(x+\frac{5}{2})}{(x-5)(x+5)}=\frac{(x-5)(x+5)}{(x-5)(x+5)}=1

 

2X^2-5x-25=0

D=25-4*2*(-25)

D=225
x1= \frac{5+15}{4}=5

x2=\frac{5-15}{4}=-\frac{5}{2}